Bisociative Knowledge Discovery: An Introduction to Concept, Algorithms, Tools, and Applications - Berthold, Michael R. (Lecture Notes in Computer Science, 2012)
Artificial Intelligence (incl. Robotics); Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet); User Interfaces and Human Computer Interaction; Pattern Recognition; Computer Communication Networks